Barriers to effective communication at the workplace / Farzana Jelani and Nur Sabrina Nordin - Jelani, Farzana; Nordin, Nur Sabrina (Akademi Pengajian Bahasa, 2019)
Working environment communication is fundamental to cooperation. In addition to the fact that it builds and look after connections, work environment communication encourages development. However, the barriers in communication can be a hindrance to information being communicated successfully. This study aims to study the communication issues that are faced by Malaysian employees in the workplace. A questionnaire was developed and distributed to Malaysian workers that comprised of various departments in Malaysia. The questionnaire comprises of questions on the communication problems in the context of the workplace in terms of language barrier and physical environment. The participants that had contributed to this study were as much as 41 respondents. The respondents involved had assessed the survey based on their personal experiences in their respective organizations. Based on the results of the study, it can be seen on how the language barrier and physical environment of the workplace affects the employees' conditions. The findings of this study can help employers view these challenges more seriously and consider the possible solutions to the problems that have been discussed. This paper is concluded by providing future researchers recommendations on various communication problems in the workplace to be further investigated and analysed in a more comprehensive manner.